The feasibility of implementing online dispute resolution as a distinct method of dispute resolution on the African continent - Cupido, Robin Vicky (Department of Commercial Law, 2025)
In a relatively short time, the internet has become woven into the fabric of society, leading to an unprecedented number of commercial and social transactions occurring across physical geographical borders. Together with this increase in online interactions comes an increase in disputes arising online, and a reliable system to resolve these issues is needed. Online Dispute Resolution (ODR) has been identified as such a system, a dispute resolution process which is in large part conducted through online systems or through the use of technology. The majority of the development, research, and scholarship of ODR has taken place and is still taking place in developed nations, often to the exclusion of the developing world. While it is acknowledged that African countries have been slow to engage with ODR as a result of various challenges, it requires investigation whether it would not be possible to promote and implement ODR in the countries that are recognised technological leaders in Africa. Through the lens of the Technology Acceptance Model, this thesis aims to explore the current state of ODR in Africa, assessing the benefits it has provided as well as the challenges that stand in the way of further adoption. South Africa, Nigeria and Kenya have been identified as technological leaders on the continent and are the subjects of a comparative study aimed at assessing their legal and technological frameworks to determine if they are ODR-ready. This study has been conducted by means of an analytical literature survey, including an analysis and exploration of legal texts, academic writing and the recommendations and reports of professional bodies. It finds that the implementation of ODR is indeed feasible in Africa, but in a different form than it is used in the Global North, using more accessible forms of technology, and expanding the use of ODR to resolve disputes arising in areas other than commercial law. The research provides guiding principles for African countries to use in assessing their readiness to adopt ODR and contributes to the ongoing scholarship of ODR with its focus on Africa, which is an aspect that has so far been relatively neglected as pre-existing scholarship centres other parts of the world.